A Critical Discourse Analysis of a Female Vice-Presidential Candidate’s Acceptance Speech - Asafo-Adjei, Ramos; Bukari, Francis; Klu, Ernest Kwasi (REiLA : Journal of Research and Innovation in Language, 2023)
This instrumental qualitative case study examined the acceptance speech of Professor Naana Jane Opoku-Agyemang, the first female vice presidential candidate of a major political party in Ghana. The study aimed to identify the discourse elements and cohesive devices used in the speech and to evaluate how she conveyed her political ideology and gender identity. Specifically, the research question was: which discourse elements and cohesive devices were employed, and how were political ideology and gender identity manifested in the speech? The data consisted of an eight-page speech delivered on July 28, 2020, in Accra, containing 3,972 words. Fairclough's (2015) Three-Dimensional textual analysis model was used for data analysis, which includes description, presentation and interpretation, and explanation of social reasons. Results showed that Professor Opoku-Agyemang used discourse elements and cohesive devices such as 'however,' 'also,' and 'second' to highlight her academic and political expertise and present herself as a qualified vice presidential candidate. She aimed to inspire women and encourage them to aspire to any position, including becoming the president of Ghana. The study's findings contribute to existing literature and can inform future research on female political representation, exposing the approaches of a marginalized group and their use of speeches to gain recognition within Ghana’s political space and beyond.